Recurrent Thyroid Storm Caused by a Complete Hydatidiform Mole in a Perimenopausal Woman. (23rd December 2020) - Jayasuriya, Anuradha; Muthukuda, Dimuthu; Dissanayake, Preethi; Subasinghe, Shyama
Abstract : Background . Gestational trophoblastic disease (GTD) which includes hydatidiform mole, invasive mole, placental site trophoblastic tumor, and choriocarcinoma is a rare cause of hyperthyroidism due to excess production of placental human chorionic gonadotrophin hormone (hCG) by tumor cells. Molecular mimicry between hCG and thyroid stimulating hormone (TSH) leads to continuous stimulation of TSH receptor by extremely high levels of hCG seen in these tumors. Consequently, biochemical and clinical hyperthyroidism ensues and it is potentially complicated by thyrotoxic crisis which is fatal unless urgent therapeutic steps are undertaken. Case Description . We present a 49-year-old perimenopausal woman who presented with recurrent thyroid storm and high output cardiac failure. The initial workup revealed suppressed TSH, high-free thyroxine (FT4), and free triiodothyronine (FT3) levels with increased vascularity of the normal-sized thyroid on ultrasonography. She was managed with parenteral beta blockers, steroids, and high-dose carbimazole. Her lower abdominal tenderness led to further investigations which revealed tremendously elevated beta-hCG and a snow storm appearance on transabdominal ultrasound suggestive of GTD. She underwent curative surgery and was diagnosed with complete hydatidiform mole postoperatively by histology. Conclusion . Recurrent thyroid crisis in gestational trophoblastic disease is an exceedingly rare presentation and that is highly fatal. This case highlights the importance of early detection and treatment of the etiology of thyrotoxicosis to eliminate mortality.